Correlation of triglyceride level with acute coronary syndrome - Islam, MZ; Faruque, M; Bari, MA; Islam, MS; Khan, MK; Khan, NA; Miah, AH; Alam, MK (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):44-48 The abstract of this article is available on the PubMed website